»Vad sanning är. får tiden visa«. Grundtvigs sanningsetik - Ehnevid, Tord (Grundtvig-Studier, 1998)
»Time must show what Truth is« Grundtvig ’s Ethics of Truth By Tord Ehnevid In 1969, at the University of Lund, I defended a doctoral thesis entitled Congregation Ethics, in which the views of Grundtvig, Morten Pontoppidan and Einar Billing were compared. Billing emphasized the sowing of the Gospel through the forgiveness of sins, Pontoppidan its harvest through »the great feeling of humanity«, and Grundtvig its growth in the congregation. But Grundtvig’s ethics seemed obscure to me which is why I continued my research into his published writings. After some years I finished the work which I called Grundtvig’s Ethics of Truth. Not until now has it been made ready for publication. The concept of growth in Grundtvig is connected with the concept of time. This is easily explained since Grundtvig took an early interest in the Northmen’s image of time, namely the ash Ygdrasil. Time grows in history from the morning of Creation. In Paradise grows the tree of life, the symbol of love, and the tree of knowledge, the symbol of truth. Through the Fall of man both love and truth are obscured for mankind, who becomes divided in two, women (love) and man (truth). In the fullness of time, God sends his son. He is the way, the truth, and the life. The Church, the work of the Holy Spirit, gathers people on to the way of truth towards the end of time, or to put it differently, on to the way of light towards eternal life. There we shall see God face to face.Another image of time is the sea with its changeability. This gives Grundtvig a place for the idea of man’s life as a look in a mirror, a riddle (l.Cor. 13), Is it the sea that is mirrored in the sky, or is it the sky that is mirrored in the sea? A third image of time is the beehive or the bell jar. People cannot get outside time, but poets and prophets may »swarm« and lead people’s thoughts and emotions outside time in words and images. The imagery is oral, living and warm. The sign of time is man as bearer of the word. The obscurity that envelops life thus becomes a riddle of the word, a riddle of man. To Grundtvig ethics is a logic of action, a chronologic. Here, too, time comes in as decisive. Time does not suffice as proof. Instead evidence is required. The proof of truth is in the evidence, the martyrdom. St. Stephen is »the bright Christ mirror«. He burned with zeal for God’s truth and with love for his fellow men. The ethics is connected to the eighth commandment. The deeds of the hand may easily lead to selfish pride. In the confession of faith the congregation may bear witness to God in common in the mother tongue. What truth is, time will show. » 0 send out thy light and thy truth: let them lead me; let them bring me unto thy holy hill, and to thy tabernacles« (Psalms 43, 3).